O‘ZBEK VA INGLIZ TILLARIDAGI “YAQIN-UZOQ” OPPOZITSIYA KOMPONENTLI FRAZEOLOGIK BIRLIKLAR TAHLILI (Scientific journal of the Fergana State University, 2024)
The study of phraseological units containing the «near-far» opposition in Uzbek and English languages offers valuable insights into the linguistic and cultural frameworks of both societies. Phraseological units, encompassing idioms, proverbs, and fixed expressions, are integral to language as they encapsulate cultural values, worldviews, and historical contexts. Analyzing these units through the lens of antonymy—specifically the “near-far” opposition—reveals how contrasting concepts are linguistically structured and culturally perceived in each language.In Uzbek and English, the “near-far” dichotomy is often employed metaphorically to express not only physical proximity or distance but also emotional, social, or conceptual relationships. For instance, in English, the phrase “a far cry” denotes a significant difference or distance from something, while in Uzbek, similar expressions might convey comparable or distinct nuances. By examining these phraseological units, scholars can gain a more nuanced appreciation of the interplay between language and culture, as well as the unique ways in which different societies conceptualize and articulate the notions of “nearness” and “farness”.